The sustainable design book - Proctor, Rebeccah (Laurence King Publishing, 2015)
"The Sustainable Design Book updates the reader on the latest products and developments in the field of green design, and features 265 of the most exciting new products around. Q&As with leading designers give insight into trends and key techniques used within the industry, while handy icons highlight each product's sustainability credentials at a glance"--Provided by publisher.